Clinical observation and dermoscopy evaluation of fractional CO2 laser combined with topical tranexamic acid in melasma treatments. (22nd February 2021) - Qu, Yan; Wang, Fengjuan; Liu, Junru; Xia, Xiujuan
Abstract: Background: Melasma is an acquired refractory pigmentary disorder, which is a skin disease that predominantly affects females. This investigation aims to assess the efficacy of a low‐power fractional CO2 laser combined with tranexamic acid (TXA) for melasma topical treatment with MASI and dermoscopy. Materials and Methods: A randomized comparative split‐face study was performed. Each treatment interval was 3 weeks with four times in total. At the same time, we applied TXA solution twice a day. Assessments were made by the MASI score of the melasma area severity index, and the dermoscopy performance was collected and analyzed. Results: After treatments, the patient MASI score decreased significantly. Compared with the baseline, the MASI score was significantly lower than that of control group ( P  < .05), and the decrease ratio was higher than that of controls. Dermoscopy examination results verified that all lesions performed reticuloglobular pattern, granular, or punctate, with no structural pigmentation and obvious capillary dilation. After comprehensive treatments, the pigmentation area displayed lighter chroma, the follicle pore uniformity was completely improved, and the capillary dilation was significantly reduced. Conclusions: Low‐power fractional CO2 laser combined with topical TXA solution is a comparatively effective and safe method for melasma treatment. TXA could reduce the dilation of blood vessels.